2017
DOI: 10.1038/s41598-017-01498-6
|View full text |Cite
|
Sign up to set email alerts
|

An optimal distance cutoff for contact-based Protein Structure Networks using side-chain centers of mass

Abstract: Proteins are highly dynamic entities attaining a myriad of different conformations. Protein side chains change their states during dynamics, causing clashes that are propagated at distal sites. A convenient formalism to analyze protein dynamics is based on network theory using Protein Structure Networks (PSNs). Despite their broad applicability, few efforts have been devoted to benchmarking PSN methods and to provide the community with best practices. In many applications, it is convenient to use the centers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 75 publications
2
62
0
Order By: Relevance
“…Distance cutoffs between 4-6Å are routinely used when examining interactions between proteins or protein-ligand pairs as most noncovalent atomic interactions are short-range (e.g., hydrogen bonds and Van der Waals interaction range from 3-4Å (Esmaielbeiki et al, 2016;Lodish et al, 2000)). For instance, a recent study on contact-based protein structure networks by Viloria and colleagues found that a distance cutoff of <5Å (heavy atoms) is most sensitive to changes in residue interactions and variables such as force fields (Salamanca Viloria et al, 2017). Therefore, we defined paratope-epitope interacting residues by a distance cutoff of <5Å between heavy atoms, i.e., amino acid residues are interacting if they have heavy atoms with a distance <5Å from each other ( Fig.…”
Section: Definition Of Interacting Residues In Antibody-antigen Complmentioning
confidence: 99%
“…Distance cutoffs between 4-6Å are routinely used when examining interactions between proteins or protein-ligand pairs as most noncovalent atomic interactions are short-range (e.g., hydrogen bonds and Van der Waals interaction range from 3-4Å (Esmaielbeiki et al, 2016;Lodish et al, 2000)). For instance, a recent study on contact-based protein structure networks by Viloria and colleagues found that a distance cutoff of <5Å (heavy atoms) is most sensitive to changes in residue interactions and variables such as force fields (Salamanca Viloria et al, 2017). Therefore, we defined paratope-epitope interacting residues by a distance cutoff of <5Å between heavy atoms, i.e., amino acid residues are interacting if they have heavy atoms with a distance <5Å from each other ( Fig.…”
Section: Definition Of Interacting Residues In Antibody-antigen Complmentioning
confidence: 99%
“…We recently applied it to the study of other cancer-related proteins, allowing to shed light on the underlying structural communication among distal sites Lambrughi et al, 2016;Papaleo et al, 2012a;Sora and Papaleo, 2019) or to help in the classification of potential cancer passenger and driver missense mutations (Nygaard et al, 2016). In details, the PSN employs the graph formalism to identify a network of interacting residues in a given protein from the number of non-covalent contacts in the protein or other intramolecular interactions Viloria et al, 2017). Two main properties of a PSN are the hub residues, i.e., residues that are highly connected within the network and the connected components, i.e., clusters of residues which are inter-connected but do not interact with residues in other clusters.…”
Section: Lc3b Ensemble Under the Lens Of Protein Structure Network: Hmentioning
confidence: 99%
“…On the contrary, if hubs are altered, the network integrity can be compromised. We calculated three PSNs, based on sidechain contacts Viloria et al, 2017), hydrogen bonds and salt-bridges (Jónsdóttir et al, 2014;Tiberti et al, 2014), respectively. We then calculated the hubs and connected components from the contact-based and hydrogen-bond based PSNs from the CHARMM22* simulation of LC3B.…”
Section: Lc3b Ensemble Under the Lens Of Protein Structure Network: Hmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the node inter-connectivity to calculate the connected components, which are clusters of connected residues in the graph. We selected 5 Å as the optimal cutoff for the contact-based PSN using the PyInKnife pipeline [87]. The distance was estimated between the center of mass of the residue side chains.…”
Section: Protein Structure Networkmentioning
confidence: 99%